2010
DOI: 10.1590/s0004-28032010000200010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the nonalcoholic fat liver disease fibrosis score for patients undergoing bariatric surgery

Abstract: -Context -Morbidly obese patients have an increased risk for nonalcoholic fat liver disease. Its severe form, nonalcoholic steatohepatitis may cause liver fibrosis. The diagnosis of advanced fibrosis has great value during the pre operative evaluation for bariatric surgery. Currently, liver biopsy is the gold standard for diagnosis of liver fibrosis. Objective -To evaluate the nonalcoholic fat liver disease fibrosis score in morbidly obese patients undergoing Roux-en-Y gastric bypass in our population. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Of these, the NAFLD fibrosis score is the most widely known nowadays. [24][25][26][27] This study showed that T2DM was significantly associated with the presence of NAFLD in a morbidly obese population.…”
Section: Discussionmentioning
confidence: 66%
“…Of these, the NAFLD fibrosis score is the most widely known nowadays. [24][25][26][27] This study showed that T2DM was significantly associated with the presence of NAFLD in a morbidly obese population.…”
Section: Discussionmentioning
confidence: 66%
“…Nine of these recruited patients from obese‐only cohorts. Five bariatric surgical studies reported liver biopsies on all bariatric surgical patients . In all studies, one or two dedicated pathologists scored all liver biopsies.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies recruited from liver disease setting ('average-obese' study), with only 12 studies recruiting specifically from settings where only obese patients are treated ('obese-only' study). These obese-only settings included bariatric or obesity clinics (7,8,15,29,32,35,40,41,(43)(44)(45)47). Demographics and baseline characteristics of obese-only cohorts were substantially different from average-obese cohorts ( Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NFS has two cut-off values used to evaluate liver fibrosis, namely, <-1.455 (low probability) and >+0.676 (high probability). According to a meta-analysis of 13 studies performed in 3,064 patients,24,25,80-91 NFS showed a high area under the receiver operating characteristic curve (AUROC) value of 0.85 in diagnosing liver fibrosis worse than stage F3. Taking <-1.455 as a cut-off, the sensitivity was 90% and the specificity was 60% in excluding advanced liver fibrosis.…”
Section: Diagnosismentioning
confidence: 99%